2012
DOI: 10.1111/j.1708-8208.2010.00289.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a New Titanium‐Zirconium Dental Implant: A Biomechanical and Histological Comparative Study in the Mini Pig

Abstract: It is concluded that the TiZr1317 implant with a hydrophilic sandblasted and acid-etched surface showed similar or even stronger bone tissue responses than the Ti control implant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
150
0
8

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(176 citation statements)
references
References 11 publications
18
150
0
8
Order By: Relevance
“…In contrast to the study of Gottlow et al (2010), we examined the dynamics of bone healing by using four different healing periods. When compared with another animal study (Thoma et al, 2011), a much more demanding and better discriminating model has been used in the present study, since the implant grooves created a standardised defect gap of 750 μm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the study of Gottlow et al (2010), we examined the dynamics of bone healing by using four different healing periods. When compared with another animal study (Thoma et al, 2011), a much more demanding and better discriminating model has been used in the present study, since the implant grooves created a standardised defect gap of 750 μm.…”
Section: Discussionmentioning
confidence: 99%
“…The physicochemical surface characteristics of Ti (SLActive) and TiZr (SLActive) implants might thus elicit different tissue responses. No signifi cant differences in BIC were found on Ti (SLActive) and TiZr (SLActive) within the grooves of cylindrical implants after 4 weeks of healing in miniature pigs (Gottlow et al, 2010) nor on standard screw-type Ti (SLActive) and TiZr (SLActive) dental implants after 2, 4 and 8 weeks of healing in dogs (Thoma et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in cases where a patient exhibits bruxism, or any other habit causing high occlusal masticatory forces, a grade 4 Cp-Ti implant, based on its standard value of static strength (yield and tensile strength), may have insufficient fatigue strength. In such cases, higher strength materials, such as titanium alloys, are necessary for dental implants [37][38][39] .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore; several materials and alloys have been tried for decades to find out the ideal biocompatibility with excellent physical features. Titanium and zirconium elements have been well documented and presented to have better tissue biocompatibilities and acceptable physical properties, when compared to others [93,94]. It is been shown that alloys of these materials can present augmented biologic and physical features while corrosion aspect of those alloys is still questionable.…”
Section: Dental Implantsmentioning
confidence: 99%